Foreign Exchange exposure and firm performance; evidence from multinational companies in Malaysia / Leslie Boni - Boni, Leslie (2019)
This paper examines the impact of exchange rate changes on the stock returns of 30 Multinational Companies (MNCs) listed on the Kuala Lumpur Stock Exchange, for the period January 2008 to June 2017. To mitigate the problem of heteroskedasticity, we use a generalized least squares estimator. The estimated regression models indicate that exchange rate variations have a significant effect on firm value and that firms are exposed significantly to one-period lagged variation in the exchange rate. Our results suggest that, in addition to exchange rate dynamics, increased exchange rate volatility appears to have significant and negative effects on firms’ stock returns. Multinational firms are likely experience greater exchange rate exposure. Finally, this paper shows that exchange rate depreciation and appreciation have significant differential effects on firms’ stock returns. The effects are very significantly towards multinational firms.